Copper loaded on activated carbon as an efficient adsorbent for removal of methylene blue. Issue 24 (3rd March 2017) - Shu, Jianhua; Cheng, Song; Xia, Hongying; Zhang, Libo; Peng, Jinhui; Li, Chunyang; Zhang, Shengzhou
Abstract : Copper loaded activated carbon (Cu-AC) was prepared by impregnating it with cupric nitrate followed by microwave heating and then used for removing dyes in wastewater. Abstract : Copper loaded activated carbon (Cu-AC) was prepared by impregnating it with cupric nitrate followed by microwave heating and then used for removing dyes in wastewater. The Cu-AC was thoroughly characterized by N2 adsorption and desorption isotherms, SEM, EDS, XRD, XPS, FT-IR, and Raman. It was proven that cupric nitrate was successfully loaded onto activated carbon with the resulting formation of copper, copper oxide, and cuprous oxide. The Cu-AC was used to treat five kinds of dyes in wastewaters (Rhodamine B, MB, Amaranth, Congo red, and Eosin-Y). Comparing the adsorption capacity of these five dye wastewaters, it was proven that copper and copper oxides have photocatalytic degradation ability that can improve dye removal efficiency. Experimental adsorption data of MB were fit using several kinetic and isotherm models. Kinetic studies indicated that a pseudo-second order is the most suitable model for the adsorption process with a correlation coefficient of R 2 > 0.999. The equilibrium adsorption data of MB showed that it followed the Langmuir isotherm; the Langmuir maximum adsorption capacity was 373 mg g −1 . Compared with ordinary activated carbon, the maximum adsorption capacity of Cu-AC increased by 37.8%. Additionally, through thermodynamic calculations the negative value of Δ G and positive value of Δ H showed that the adsorption was a spontaneous and endothermic process. All the above results reveal that Cu-AC can be an effective absorbent for removing dyes from wastewater.